Percutaneous cheilectomy combined with Watermann and Moberg osteotomies for the treatment of hallux rigidus - Arruda, Júlio Ferreira de; Baptista, André Donato (Scientific Journal of the Foot & Ankle, 2019)
Objective: To evaluate the clinical and functional outcomes of patients subjected to surgical treatment of hallux rigidus by the percutaneous cheilectomy combined with Watermann and Moberg osteotomies. Methods: Between May 2017 and August 2018, the clinical outcomes of 7 patients with a diagnosis of hallux rigidus (HR) treated using the percutaneous technique were assessed using the American Orthopedic Foot and Ankle Society (AOFAS) scale, the visual analogue scale (VAS) for pain and hallux metatarsophalangeal joint range of motion measurements during the pre- and postoperative periods. Clinical and functional outcomes were followed up for a minimum of 6 months (mean of 8 months). Results: The range of motion of the metatarsophalangeal joint during the pre- and postoperative periods showed the following results: dorsiflexion increased on average from 28.00º (± 15.63) to 44.43º (± 17.33) (p = 0.006), demonstrating an effective gain in dorsal articular movement. Plantar flexion ranged on average from 27.43º (± 2.22) to 24.43º (± 5.28) (p = 0.228), with no significant difference between the evaluated periods. The AOFAS score increased on average from 52.71 (± 9.63) to 88.00 (± 8.10) (p < 0.01), representing important functional improvement. The VAS score decreased on average from 7.00 (± 1.52) to 2.14 (± 2.19) (p = 0.002), indicating a significant improvement in patient pain. No patient presented postoperative complications. Conclusion: The results of the present study demonstrated that cheilectomy combined with percutaneous Watermann and Moberg osteotomies is an effective surgical treatment for hallux rigidus, with satisfactory clinical and functional outcomes. Level of Evidence IV; Therapeutic Studies; Case Series.